Lambda display phage as a mucosal vaccine delivery vehicle for peptide antigens. Issue 52 (19th December 2017) - Cano, Patricia González; Gamage, Lakshman N.A.; Marciniuk, Kristen; Hayes, Connie; Napper, Scott; Hayes, Sidney; Griebel, Philip J.
Highlights: Lambda phage can display multiple peptide epitopes on capsid head protein D. Lambda phage uptake from the small intestine occurs primarily through Peyer's patches. Lambda phage induce phage-specific IgA antibody responses in Peyer's patches. Lambda phage displaying peptide epitopes induce epitope-specific IgA antibody responses Phage displaying peptide epitopes induce IgA responses in the absence of adjuvants. Abstract: Bacteriophage are structurally stable in the gastro-intestinal tract and have favorable traits of safety, stability, ease of production, and immunogenicity. These attributes make them potential candidates as oral vaccine delivery vehicles but little is known about their capacity to induce mucosal immune responses in the small intestine. Whole body imaging of mice confirmed lambda bacteriophage (LP) were distributed throughout the gastro-intestinal tract 24 h after oral delivery. In newborn calves, targeted delivery of LP within the small intestine confirmed LP were immunogenic in a dose-dependent manner and were taken up by Peyer's patches. LP-specific IgA responses were induced within both Peyer's patches and draining mesenteric lymph nodes. A lambda display phage (LDP) was constructed to present three immunogenic disease specific epitopes (DSE) from cervid prion protein (amino acids 130–140 [YML]; 163–170 [YRR]; and 171–178[YRR]) fused to phage capsid head protein D (LDP-DSE). Targeted delivery of purified LDP-DSE to intestinal segments induced IgA responses to all three peptide epitopes. Further, delivery of bacteria expressing soluble D-DSE also induced epitope-specific IgA responses in the targeted Peyer's patches. These are the first studies to report use of LDP to induce epitope-specific IgA responses in the small intestine and confirm Peyer's patches function as a site for LP uptake. Furthermore, IgA responses to peptide epitopes on LDP were observed in the absence of a mucosal adjuvant. These observations confirm LDP have the capacity to function as a mucosal delivery vehicle with protein D as an effective carrier for peptide epitopes.